2003
DOI: 10.1183/09031936.03.00052002
|View full text |Cite|
|
Sign up to set email alerts
|

Xanthine oxidase inhibition reduces reactive nitrogen species production in COPD airways

Abstract: Reactive nitrogen species (RNS) have been reported to be involved in the inflammatory process in chronic obstructive pulmonary disease (COPD). However, there are no studies on the modulation of RNS in COPD. It was hypothesised that inhibition of xanthine oxidase (XO) might decrease RNS production in COPD airways through the suppression of superoxide anion production.Ten COPD and six healthy subjects participated in the study. The XO inhibitor allopurinol (300 mg?day -1 p.o. for 4 weeks) was administered to COP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
40
1
1

Year Published

2003
2003
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(42 citation statements)
references
References 31 publications
0
40
1
1
Order By: Relevance
“…Mild steroid-naïve asthmatics had significantly higher levels of NT than healthy controls but levels were reduced in those treated with ICS with moderate and severe disease [78]. Although NT measurements have been performed in induced sputum of COPD patients, with increased levels compared with controls and inhibition by the xanthine oxidase inhibitor allopurinol, there have been no studies using this method in EBC from COPD patients [96]. Nitrosothiols Diagnosis Nitrosothiols (RS-NO) are measured using a commercially available assay (Oxonon; detection limit 0.025 mM) based on the cleavage of RS-NO to release NO, which upon rapid oxidation forms NO 2 -and is detected colourimetrically.…”
Section: Clinical Trialsmentioning
confidence: 99%
“…Mild steroid-naïve asthmatics had significantly higher levels of NT than healthy controls but levels were reduced in those treated with ICS with moderate and severe disease [78]. Although NT measurements have been performed in induced sputum of COPD patients, with increased levels compared with controls and inhibition by the xanthine oxidase inhibitor allopurinol, there have been no studies using this method in EBC from COPD patients [96]. Nitrosothiols Diagnosis Nitrosothiols (RS-NO) are measured using a commercially available assay (Oxonon; detection limit 0.025 mM) based on the cleavage of RS-NO to release NO, which upon rapid oxidation forms NO 2 -and is detected colourimetrically.…”
Section: Clinical Trialsmentioning
confidence: 99%
“…As the xanthine oxidase inhibitor reduces the reactive nitrogen species production, this agent may be useful for reducing the inflammatory and destructive process in COPD ( Fig. 1) (16).…”
Section: Future Therapy For Copdmentioning
confidence: 99%
“…As discussed in the paper by ICHINOSE et al [1], there are multiple mechanisms to form O 2 -, one of which is XO. The authors identified that in subjects with COPD, the XO activity in induced sputum was four-fold higher than controls, and that this activity was effectively reduced by allopurinol.…”
mentioning
confidence: 98%
“…INCHINOSE et al [1] in this issue of European Respiratory Journal, have in part overcome this hurdle. They measure only three components of the lung redox system (xanthine oxidase (XO), NO, and nitrotyrosine), by necessity leaving the remainder unassessed.…”
mentioning
confidence: 99%
See 1 more Smart Citation